2003
DOI: 10.1007/s00125-003-1116-6
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from heart disease in a cohort of 23,000 patients with insulin-treated diabetes

Abstract: Aims/hypothesis. Although ischaemic heart disease is the predominant cause of mortality in older people with diabetes, age-specific mortality rates have not been published for patients with Type 1 diabetes. The Diabetes UK cohort, essentially one of patients with Type 1 diabetes, now has sufficient follow-up to report all heart disease, and specifically ischaemic heart disease, mortality rates by age. Methods. A cohort of 23,751 patients with insulintreated diabetes, diagnosed under the age of 30 years and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
407
2
26

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(459 citation statements)
references
References 26 publications
16
407
2
26
Order By: Relevance
“…Data from the WESDR and the Hvidore hospital studies [3,4,9] were not included in this analysis since baseline values for CAD cases and non-cases are not currently published.…”
Section: Comparative Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the WESDR and the Hvidore hospital studies [3,4,9] were not included in this analysis since baseline values for CAD cases and non-cases are not currently published.…”
Section: Comparative Study Selectionmentioning
confidence: 99%
“…These observations are especially true for those with type 1 diabetes mellitus, in whom coronary heart disease is increased tenfold or greater [2,3]. However, while the role of glycaemia in the development of microvascular diabetes complications, such as retinopathy and albuminuria, is well established [4,5], its role in CVD in patients with type 1 diabetes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The increased cardiovascular disease (CVD) risk in individuals with diabetes mellitus cannot be fully explained by traditional cardiovascular risk factors [1,2]. Therefore, other factors and mechanisms potentially involved need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that type 1 diabetic children and adolescents have an increased risk of cardiovascular disease compared to the general population [1,2]. The multi-centre study EURODIAB found that low intake of saturated fat and high intake of fibre reduced the risk of cardiovascular disease among type 1 diabetic subjects [3,4].…”
Section: Introductionmentioning
confidence: 99%